Air Pollution, Energy Consumption and Economic Growth in Iran - Mohammadhassan Fotros (Pizhūhishnāmah-i Iqtiṣād-i Inirzhī-i Īrān, 2011)
This research investigates the existence and direction of Granger causality between economic growth, energy consumption, and carbon emissions in Iran. A multivariate model including economic growth, energy consumption, carbon emissions, capital stock, labor force, and urban population is used to determine eventual causality between variables according to Toda-Yamamoto Approach. Results indicate that there is a bi-directional causality relationship between gross domestic product and CO2 emissions. Also, there is a uni-direction causality relationship from energy consumption to CO2 emissions. Finally, the results maintain that the EKC hypothesis for GDP and CO2 emissions is relevant in the period of study.